Why Is the Business-Cycle Behavior of Fundamentals Alike Across Exchange-Rate Regimes? - Luca Dedola; Sylvain Leduc (Oesterreichische Nationalbank (OeNB), 2001)
Since the adoption of flexible exchange rates, real exchange rates have been much more volatile than they were under Bretton Woods. However, the volatilities of most other macroeconomic variables have remained approximately unchanged. This poses a puzzle for standard international business cycle models. This paper develops a two-country, two-sector model with nominal rigidities featuring deviations from the law of one price due to firms setting prices in buyers' currencies. By partially insulating goods markets across countries and thus mitigating the international expenditure-switching effect, this pricing behavior is found to considerably dampen the responses of quantities to shocks hitting the economies therefore helping to account for the puzzle.
Keywords: E32; E52; F31; F33; F41; 330